Depiction of work in ephemeral key: vendimiales stages and exhibition halls in Mendoza (Argentina), 1946-1955 - Marchionni, Franco; Laboratorio de Desertificación y Ordenamiento Territorial (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
The look proposal outlined in the custody of tangible and intangible resources that allow us to observe the exerciseof power of the various actors involved in the design of the representations of work. From the study of scenariosvendimiales and exhibition halls used by the Peronist propaganda machine is trying to rebuild a look that says thedeliberate action of Peronism to feed the imagination around the representations of work for the “New Argentina”.This work is developed within the historical method and is based on the analysis of two types of ephemeral architecture:vendimiales scenarios and exhibition halls. These ideas and representations are linked with the analysis ofpolitical and ideological context of the Peronist administration. The methodological strategy used is qualitative andexploratory, with a design of a flexible nature (Valles, 2000).